2016
DOI: 10.6026/97320630012019
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of Pistacia atlantica leaf extract

Abstract: The antimicrobial effect of the mastic tree (Pistacia atlantica) under in vitro conditions has been reported. Therefore, it is of interest to evaluate the effect of the plant leaf extract (aqueous) on bacterial load in mouth and saliva. The leaf of the Pistacia atlantica plant was collected and cleaned, dried at 40⁰c and then powdered. The extraction was carried out using the maceration method in vacuum with the rotary evaporator device. Bacterial inhibition (Streptococcus species) by the leaf extract was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Our results showed inhibitory activity in the aqueous extract for Pistacia atlantica against plant pathogenic bacteria Erwinia carotovora, the diameters of the inhibition zone was 7.67, 10, 10.67 and 12 mm for concentrations of 20, 40, 80, 100% respectively, and this corresponds with some of the previous research [42,43]. The antibacterial activity of the extracts of P. atlantica may be due to the presence of certain antimicrobial secondary metabolite, the leaf extract is rich in phenol compounds which have a high level of antibacterial properties against plant pathogens [44,45].…”
Section: Resultssupporting
confidence: 91%
“…Our results showed inhibitory activity in the aqueous extract for Pistacia atlantica against plant pathogenic bacteria Erwinia carotovora, the diameters of the inhibition zone was 7.67, 10, 10.67 and 12 mm for concentrations of 20, 40, 80, 100% respectively, and this corresponds with some of the previous research [42,43]. The antibacterial activity of the extracts of P. atlantica may be due to the presence of certain antimicrobial secondary metabolite, the leaf extract is rich in phenol compounds which have a high level of antibacterial properties against plant pathogens [44,45].…”
Section: Resultssupporting
confidence: 91%
“…These plants were: Moringa peregrina, Pistacia atlantica, Eucalyptus camaldulensis, Acacia cyanophylla and Ceratonia silique. These plants were selected due to their potential as antiviral agents since their antimicrobial activities have been reported (Cimanga et al, 2002;Kivack et al, 2002;Ayeb-Zakhama et al, 2015;Roozegar et al, 2016). Moreover, these plants are distributed worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Following the same criteria cited earlier (MIC  100 μg/mL and r=1) and establishing the best products reported in literature, Glycyrrhiza uralensis deglycyrrhizinated licorice root extract (Ahn et al, 2012), Mikania glomerate ent-Kaurenoic acid-rich extract (Moreira et al, 2016b), Ipomoea alba chloroform fraction (Silva et al, 2014), and Pistacia atlantica aqueous extract (Roozegar et al, 2016) showed the best results. Considering isolated substances and criteria established here, only saponin class showed important results.…”
Section: Resultsmentioning
confidence: 65%